OPTIMIZATION OF THE HUMAN RESOURCE TRANSFER AND PROMOTION SYSTEM FOR PROPER JOB PLACEMENT TO SUPPORT ORGANIZATIONAL PERFORMANCE - Aji Widayat, Moch; Hardiman , Hardiman (Cognitionis Civitatis et Politicae, 2026)
Human resource (HR) management plays a pivotal role in achieving organizational goals by ensuring the right people are placed in the right roles. The optimization of HR transfer and promotion systems is critical to fostering employee satisfaction and organizational performance. However, many organizations face challenges in aligning HR processes with strategic objectives, leading to inefficiencies in job placement and performance. This study investigates the optimization of HR transfer and promotion systems to enhance job placement accuracy and support organizational performance. The research aims to analyze existing HR practices, identify key factors influencing job placement, and propose an optimized framework that aligns employee capabilities with organizational goals. A mixed-method approach was employed, combining qualitative case studies, expert interviews, and quantitative surveys. The findings reveal that organizations with structured and transparent HR systems experience higher employee satisfaction and better alignment between individual skills and job roles. In contrast, organizations with informal HR processes face misalignments, lower engagement, and suboptimal performance. The study concludes that formalizing HR transfer and promotion systems is essential for improving job fit, boosting employee satisfaction, and enhancing organizational performance. The research provides actionable recommendations for organizations to optimize HR practices and contribute to long-term success.